1997
DOI: 10.1164/ajrccm.155.2.9032203
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal skeletal muscle oxidative capacity after lung transplantation by 31P-MRS.

Abstract: Although lung transplantation improves exercise capacity by removal of a ventilatory limitation, recipients' postoperative maximum oxygen uptake (VO2max) remains markedly abnormal. To determine if abnormal skeletal muscle oxidative capacity contributes to this impaired aerobic capacity, nine lung transplant recipients and eight healthy volunteers performed incremental quadriceps exercise to exhaustion with simultaneous measurements of pulmonary gas exchange, minute ventilation, blood lactate, and quadriceps mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 36 publications
4
53
0
2
Order By: Relevance
“…For example, systemic steroids, frequently prescribed pre-and post-LTx, may induce atrophy and myopathy in all peripheral muscles. 7 Our data also show a significant, but weak correlation between time on the waiting list and muscle force of the quadriceps 1 year after transplantation. This correlation suggests that lung transplant recipients with a long waiting period have less muscle force 1 year after transplantation.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…For example, systemic steroids, frequently prescribed pre-and post-LTx, may induce atrophy and myopathy in all peripheral muscles. 7 Our data also show a significant, but weak correlation between time on the waiting list and muscle force of the quadriceps 1 year after transplantation. This correlation suggests that lung transplant recipients with a long waiting period have less muscle force 1 year after transplantation.…”
Section: Discussionsupporting
confidence: 49%
“…6 Reduced oxygen utilization by the vastus lateralis muscle was demonstrated after LTx by 31-phosphorus ( 31 P)-magnetic resonance spectroscopy and by optical near-infrared spectroscopy. 7,8 Skeletal muscle biopsies from the quadriceps exhibited lower activity of the oxidative enzymes, lower proportion of type 1 (fatigue-resistant) fibers, higher lactate concentration, low intramyocyte pH, and reduced adenosine triphosphate (ATP) content. 9 Together, these studies support the hypothesis that the limited exercise capacity found after LTx may be due, at least in part, to limited muscle strength and limited endurance capacity of the lower limbs.…”
mentioning
confidence: 99%
“…Another observation that points to the significance of muscle weakness in limiting exercise capacity is that, in spite of significant differences in lung function measurements, no significant differences were seen in post-transplant exercise capacity between single or double lung transplantation [44]. This may partly be explained by the fact that peripheral muscle weakness or dysfunction plays an important role in exercise limitation in these patients [45]. Finally, MALTAIS et al [25] observed significant reductions in oxidative capacity of the peripheral muscles in COPD patients.…”
Section: Peripheral Muscle Trainingmentioning
confidence: 99%
“…Factors responsible for this muscle dysfunction may include pretransplant deconditioning, chronic steroid intake, cyclosporin-induced mitochondrial myopathy, and muscle wasting, in particular in patients with cystic fibrosis [2, 19,26,27]. Peripheral muscle dysfunction may also account for the early anaerobiosis and the associated hyperventilation which were observed in the current patients.…”
Section: Discussionmentioning
confidence: 99%